PENERAPAN ENTERPRISE RESOURCE PLANNING DALAM MENUNJANG SISTEM INFORMASI MANAJEMEN PADA MADRASAH ALIYAH AL – UMMAH PANDANWANGI - Mohamad Arif Rahman Hakim; Achmad Imam Agung; Ginanjar Setyo Permadi; Anita Andriani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Rapid advancement of information technology necessitates that educational institutions implement integrated systems to enhance efficiency and streamline data management. Madrasah Aliyah Al-Ummah Pandanwangi, a private senior high school, previously handled its data manually and in isolation across departments, leading to inefficiencies and data duplication. This study proposes the adoption blonging to a Management Information System which that is interegered using Enterprise Resource Planning (ERP) system to unify academic, administrative, and infrastructural processes. Utilizing an experimental approach, the ERP system was developed in several stages requirements assesment, designing that system, deployment, evaluation, and upkeep. That system features various modules designed for school principals, administrative personnel, curriculum management, student affairs, counseling, facilities, teachers, and students. findings reveal significant improvements in operational efficiency, data transparency, and decision-making speed, enabled by real-time access and centralized management. ERP-based system effectively promotes systematic and accountable school administration, providing a replicable model for broader application in other educational institutions.